Influence Of Aircraft Engine Exhaust Emissions At A Global Level And Preventive Measures - Jasna Golubić; Velimir Kolar; Tomislav Župić (Promet - Traffic&Transportation, 1970)
The work considers the differences in the aircraft engine exhaustemissions, as well as the impact of the emissions on theenvironment depending on several factors. These include theage of the engine, i. e. technical refinement, engine operating regimesat different thrusts during time periods: takeoff, climb,approach, etc. Also, the exhaust emissions do not have thesame influence on different atmospheric layers. The pollutantsemitted at higher altitudes during cruising have become agreater problem, although the volume of pollutants is smaller,due to the chemical complexity and sensitivity of these layers ascompared to the lower layers of atmosphere. One of the reasonswhy these problems have long remained outside the focus of interestof the environmentalists is that the air transport of goodsand people is performed at high altitudes, so that the pollutionof atmosphere does not present a direct threat to anyone, sincethe environment is being polluted at a global level and thereforeis more difficult to notice at the local level.